2005
DOI: 10.1007/bf03015775
|View full text |Cite
|
Sign up to set email alerts
|

The Proseal™ LMA is a useful rescue device during failed rapid sequence intubation: two additional cases

Abstract: P Pu ur rp po os se e: : We report two cases where the ProSeal™ laryngeal mask airway (PLMA) was successfully used as a rescue device, after failed tracheal intubation, during rapid sequence induction.C Cl li in ni ic ca al l f fi in nd di in ng gs s: : The first case involved a 31-yr-old primigravida presenting for emergency Cesarean section for severe fetal distress. She had a grade 3 larynx and airway edema was observed during laryngoscopy. Attempts with a McCoy blade and gum elastic bougie failed to secure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0
3

Year Published

2005
2005
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 28 publications
0
29
0
3
Order By: Relevance
“…8,9 More recent studies and case reports have shown that it is effective in providing ventilation and oxygenation in challenging cases, such as the morbidly obese patients, 10 patients in the prone position, 11,12 and those who have suffered from multiple trauma. 13 The use of the PLMA as an airway device in emergency Cesarean deliveries has been reported in case series and case reports, [14][15][16][17][18] and it has been used without adverse effects for postpartum tubal ligation. 19 Our prospective observational study aims to evaluate the role of the SLMA in providing ventilation and oxygenation in carefully selected parturients undergoing lower segment Cesarean delivery under general anesthesia after at least four hours of fasting.…”
Section: Résumémentioning
confidence: 99%
“…8,9 More recent studies and case reports have shown that it is effective in providing ventilation and oxygenation in challenging cases, such as the morbidly obese patients, 10 patients in the prone position, 11,12 and those who have suffered from multiple trauma. 13 The use of the PLMA as an airway device in emergency Cesarean deliveries has been reported in case series and case reports, [14][15][16][17][18] and it has been used without adverse effects for postpartum tubal ligation. 19 Our prospective observational study aims to evaluate the role of the SLMA in providing ventilation and oxygenation in carefully selected parturients undergoing lower segment Cesarean delivery under general anesthesia after at least four hours of fasting.…”
Section: Résumémentioning
confidence: 99%
“…Also the ILMA, designed especially for the management of the difficult airway, has been described as being successfully used for ventilation in the anticipated [26][27][28][29][30][31][32] and unanticipated [33,34] difficult airway in 97-100% of cases. Case reports or series (level 4) of successful ventilation in patients with difficult airways have been described for many other SADs: the LMA PLMA [35][36][37][38][39][40][41], the SLMA [42][43][44], the i-gel [45][46][47][48][49][50], the Ambu-i TM [51], the Air-Q [52][53][54][55], the CobraPLA [56] and the CobraPLUS [57]. The Laryngeal Tube, designed for emergency ventilation, is also successfully described in difficult airway management in elective adult [58] and paediatric [59] patients in the operation room.…”
Section: Ventilation Via Different Sads In a Difficult To Manage Airwaymentioning
confidence: 99%
“…[86][87][88][89] On six occasions the PLMA secured airway rescue after failed intubation at rapid sequence induction (RSI). [90][91][92][93][94] Four were obstetric emergencies [91][92][93][94] and two non-obstetric. 90,91 Three cases were associated with difficult ventilation.…”
Section: Difficult Airwaysmentioning
confidence: 99%
“…[90][91][92][93][94] Four were obstetric emergencies [91][92][93][94] and two non-obstetric. 90,91 Three cases were associated with difficult ventilation. 90,91 In two cases rescue with a cLMA was attempted but failed before a PLMA was used.…”
Section: Difficult Airwaysmentioning
confidence: 99%
See 1 more Smart Citation